Adaptation and validation of the teacher job performance scale for indonesian teachers - Liliza Agustin; Wan Nurul Izza Wan Husin (SUKMA : Jurnal Penelitian Psikologi, 2026)
This study aimed to adapt and validate the Teacher Job Performance Scale (TJPS) for use among Indonesian teachers. The original TJPS developed by Limon and Sezgin-Nartgün (2020) was selected because it offers a multidimensional framework for assessing teacher performance through task performance, contextual performance, and adaptive performance. The adaptation process involved forward translation, expert review, back-translation, focus group discussion, readability testing, and psychometric validation. Data were collected from 202 in-service teachers in Indonesia and analyzed using Confirmatory Factor Analysis (CFA) with AMOS. The initial scale consisted of 37 items, including 16 task performance items, 9 contextual performance items, and 12 adaptive performance items. Four items (TP1, TP2, TP10, and CP9) showed standardized loadings below .50 and were removed. The final 33-item model demonstrated acceptable factor loadings (.511-.960), high construct reliability (CR = .982), and adequate convergent validity (AVE = .625). The overall model fit was acceptable, with χ² = 1993.450, df = 492, χ²/df = 4.052, RMSEA = .078, and CFI = .900. These findings indicate that the Indonesian adaptation of the TJPS is a psychometrically acceptable instrument for assessing teacher job performance, although further validation using broader and more diverse samples is recommended.   Penelitian ini bertujuan untuk mengadaptasi dan memvalidasi Teacher Job Performance Scale (TJPS) agar dapat digunakan pada guru di Indonesia. TJPS yang dikembangkan oleh Limon dan Sezgin-Nartgün (2020) dipilih karena memiliki kerangka multidimensi yang mengukur kinerja guru melalui tiga dimensi, yaitu task performance, contextual performance, dan adaptive performance. Proses adaptasi mencakup penerjemahan, telaah pakar, penerjemahan balik, diskusi kelompok terfokus, uji keterbacaan, dan validasi psikometrik. Data diperoleh dari 202 guru di Indonesia dan dianalisis menggunakan Confirmatory Factor Analysis (CFA) melalui AMOS. Skala awal terdiri atas 37 item, yaitu 16 item task performance, 9 item contextual performance, dan 12 item adaptive performance. Empat item, yaitu TP1, TP2, TP10, dan CP9, memiliki nilai loading terstandar di bawah 0,50 sehingga dikeluarkan dari model. Model akhir dengan 33 item menunjukkan nilai loading yang memadai, yaitu antara 0,511 hingga 0,960, reliabilitas konstruk yang tinggi (CR = 0,982), serta validitas konvergen yang memadai (AVE = 0,625). Indeks kesesuaian model berada pada tingkat yang dapat diterima, yaitu χ² = 1993,450, df = 492, χ²/df = 4,052, RMSEA = 0,078, dan CFI = 0,900. Temuan ini menunjukkan bahwa TJPS versi Indonesia merupakan instrumen yang dapat diterima secara psikometrik untuk mengukur kinerja guru, meskipun validasi lanjutan dengan sampel yang lebih luas masih diperlukan.